Statistical Analysis of Factors for Changes in Student Behavior in Solo Raya as a Catalyst for Empowerment of Waste Banks: The Role of Agents of Change - Ardiana, Vina; Hakim, Fikrul; Dirgantara, I Made Bayu; Hidayati, Retno (GoAcademica Research & Publishing, 2024)
Overcoming the substantial waste issue in Indonesia poses a significant challenge. The establishment of waste banks is identified as a potential solution, yet there needs to be more active community engagement in becoming waste bank patrons. Hence, this study aims to identify factors influencing individuals' behaviors in supporting waste bank empowerment. The research adopts the Theory of Planned Behavior, encompassing six variables: attitudes, subjective norms, knowledge, financial motives, intentions, and behavior. Questionnaires were distributed via social media for data collection, with 200 respondents selected through purposive sampling, primarily active students at the University in Solo Raya the analysis employed multiple linear analysis to assess the significance of the regression model, coefficient of determination, and the partial influence of each variable. Findings indicate that subjective norms and financial motives positively influence intentions, though not significantly. Conversely, attitude and knowledge variables significantly and positively impact intentions. Additionally, the intention variable demonstrates a significant positive effect on behavior supporting waste bank empowerment.